USES AND GRATIFICATIONS OF GENTA MAGAZINES AMONG PETRA CHRISTIAN UNIVERSITY’S STUDENT - Felicia Luvena; Veronica Maureen; Fanny Lesmana (Universitas Bunda Mulia, 2019)
ABSTRACTGENTA Magazine was published by student press known as Pers Mahasiswa (PERSMA) of Petra Christian University since January 28th, 1964 and also the oldest campus magazine in Indonesia. GENTA Magazine intended for Petra Christian University community. But, because it is made by the student press, in this paper we tried to focus on the student audience. In principle, GENTA Magazine is an internal media. The study aimed to know about GENTA Magazine's reader’s gratifications, especially the students of Petra Christian University. The students were asked to rate their reason to read GENTA Magazine based on those statements that operationalized in 5-point Likert scale (5=exactly, 1=not at all). The instrument was divided into two parts: the first part, they were asked to answer basic identity (gender and major). And in the final section they were asked about motivations in reading GENTA Magazine that divided again into 3 categories based on Stafford, Stafford & Schkade (2004) meta-categorization of gratification factors (Social Gratifications, Content Gratifications, and Process Gratifications). This research will be value-able to the magazines publishers to adapt with their audience motives and needs from the magazines. The student press, as the publishers might have more understanding of how to make their contents of the magazine and have better understanding how of how to get the audience attention’s. The findings revealed that Petra Christian University's students’ gratifications are fulfilled in content gratification indicatorKeywords; magazine, media consumptions, uses and gratifications.ABSTRAKMajalah GENTA diterbitkan oleh pers mahasiswa yang dikenal sebagai Pers Mahasiswa (PERSMA) Universitas Kristen Petra sejak 28 Januari 1964 dan juga majalah kampus tertua di Indonesia. Majalah GENTA ditujukan untuk komunitas Universitas Kristen Petra. Tetapi, karena dibuat oleh pers siswa, dalam makalah ini kami mencoba untuk fokus pada audiensi siswa. Pada prinsipnya, Majalah GENTA adalah media internal. Penelitian ini bertujuan untuk mengetahui tentang kepuasan pembaca Majalah GENTA, terutama mahasiswa Universitas Kristen Petra. Para siswa diminta untuk menilai alasan mereka untuk membaca Majalah GENTA berdasarkan pernyataan-pernyataan yang dioperasionalkan dalam skala Likert 5 poin (5 = tepatnya, 1 = tidak sama sekali). Instrumen ini dibagi menjadi dua bagian: bagian pertama, mereka diminta untuk menjawab identitas dasar (gender dan utama). Dan pada bagian terakhir mereka ditanya tentang motivasi dalam membaca Majalah GENTA yang dibagi lagi menjadi 3 kategori berdasarkan meta-kategorisasi faktor-faktor kepuasan(Gratifikasi Sosial, Gratifikasi Konten, dan Gratifikasi Proses). Penelitian ini akan bermanfaat bagi penerbit majalah untuk beradaptasi dengan motif dan kebutuhan audiens mereka dari majalah tersebut. Pers mahasiswa, karena penerbit mungkin memiliki lebih banyak pemahaman tentang bagaimana membuat konten majalah mereka dan memiliki pemahaman yang lebih baik tentang bagaimana cara mendapatkan perhatian penonton. Temuan mengungkapkan bahwa gratifikasi mahasiswa Universitas Kristen Petra terpenuhi dalam indikator kepuasan kontenKata kunci: majalah, konsumsi media, penggunaan dan kepuasan.